Building Climate Adaptation Pathways: Community Tools and Planning in Yala Wetlands, Kenya - Akwany, Leonard; Adhiambo, Roniance; Ogoma, Maurice O. (Geography, Earth Science and Environment: Research Highlights Vol. 3, 2025)
Yala Wetlands is a critical ecosystem that filters water from the Nzoia and Yala Rivers into Lake Victoria and supports local communities which rely on artisanal fishing and small-scale agriculture. However, the wetland is increasingly threatened by human activities and climate change. This study applied the Community Climate Change Adaptation Assessment (C3A2) approach, using eight participatory tools including climate risk mapping, vulnerability assessments, and stakeholder analysis, to identify resilient community-level adaptation strategies for climate adaptation planning. Two tools were applied at the Siaya County level, while all eight were utilized at the community level. Data were collected from eighty respondents through interviews and focus group discussions, with analysis conducted at multiple stages. The study revealed that drought and floods were the most significant climate risks, disproportionately affecting vulnerable households. Agroforestry was identified as an effective strategy for mitigating drought and flood impacts, while ecotourism emerged as a viable solution for addressing human-wildlife conflict. The development of three Community-Based Adaptation Action Plans (CBAPs) led to the initiation of community-led projects, such as water harvesting and an agroforestry demonstration farm. The findings underscore the effectiveness of the C3A2 approach in creating locally accepted, resilient adaptation plans although site-specific adjustments are necessary for its broader application. The outcomes of the study have important implications for policy and practice, particularly in integrating community-driven strategies into broader climate adaptation frameworks. They also provide a foundation for future research in enhancing community resilience to climate change.